Instrumental rationality and power on nature. From antisemitism to social networks - Mandara, Luca (Mechane, 2025)
The paper deals with the manifestation of mimetic tendencies within social networks. Retracing the dialectic between “technique” and “nature” outlined by Max Horkheimer and Theodor W. Adorno, the paper argues that such tendencies are not the absolute “irrational” outside, but the other side of the very specific form of rationality embodied by these technologies, which share the same contradictory features of the Western monopoly and financial capitalism. In the end, the paper would also inquiry the possibility of diverging the mimetic impulses from the regressive identification with authoritarian leaders toward progressive politics of emancipation.